PENENTUAN JARAK TERDEKAT WISATA KULINER MENGGUNAKAN ALGORITMA DI JKSTRA - Kusnanto, Romario; Handoko, Koko (LPPM Universitas Putera Batam, 2021)
Batam city is a city where many travelers passsing from local or overseas because it’s situated between Singapore and Malaysia so this city responsible to accommodate people such as hotel, although it’s high but there’s no tourism destination place that made travelers facing trouble to decide shortest path. Dijkstra’s algorithm is the answer for solving shortest path problem to our location. We can use present technology to decide which way is nearest with Google Map, but present technology doesn’t ensure us to give the best answer. Research about determination of closest distance culinary place using dijkstra’s algorithm with Open Street Map as the data source is conducted to see or compare the result from Google Map. The data in OSM is obtained by OSMnx, newest tool to capture data such as map and show visual of map. OSMnx can obtain data with ease by coding using python. The data result as visual between Google Map and OSMnx are same so OSMnx can give answer for choosing the shortest path, and accuracy of OSMnx to show the data is 85,7%.